Sermaye birikiminin sürekliliği ve Türkiye'de özelleştirme : Petrol Ofisi A.Ş. (POAŞ) örneği - Süzük, Mehmet Aşkın (My University, 2019)
Türkiye’de sermaye birikimi sürecinde devlet, KİT’ler aracılığıyla önemli bir işlev görmüş ve girişimci rolüyle ekonomiye doğrudan müdahale etmiştir. 1930’lu yıllarda planlı dönemde kurulmaya başlanan KİT’lerin hem kuruluş gerekçelerinin hem de faaliyetlerinin sermaye birikimi ihtiyaçları doğrultusunda belirlendiği görülmektedir. Aynı kuruluşların özelleştirme takvimleri ve süreçleri de aynı ihtiyaçlar ile şekillendirilmiştir. Bu durum, KİT’lerin kurulmasının ve faaliyetlerinin, daha sonra belli bir plan dahilinde özelleştirilmelerinin sermaye birikiminin sürekliliği çerçevesinde incelenip anlaşılabileceğini göstermektedir. Bu çalışma, akaryakıt dağıtım sektöründe faaliyet yürütmek amacıyla 1941 yılında devlet eliyle kurulan Petrol Ofisi’nin faaliyetlerini ve özelleştirilmesini bu çerçevede değerlendirmeyi amaçlamaktadır. Çalışmada, farklı sermaye birikim rejimleri içerisinde Petrol Ofisi’nin faaliyetleri ve misyonları ortaya konulmakta, özelleştirme süreçlerine ve özelleştirmenin sonuçlarına bir bütün olarak odaklanılmaktadır.

In the capital accumulation process in Turkey, the government has fulfilled a significant function through State Economic Enterprises, and directly intervened in the economy with the entrepreneur role. It is seen that both reasons of establishment and activities of the State Economic Enterprises, which were started to be established in the planned period in 1930s, were determined in line with the needs of capital accumulation. Also the privatisation schedules and processes of the same enterprises were shaped by the same needs. This situation shows that the establishment and activities of the State Economic Enterprises, and later on their privatisation could be examined and understood within the framework of the continuity of capital accumulation. In this context, this study aims to evaluate the activities and privatisation of Petrol Ofisi, which was established by the state in 1941 with the purpose of operating in fuel distribution sector. In the study, the activities and missions of Petrol Ofisi among different capital accumulation regimes are set forth, and the privatisation processes and the consequences of privatisation are focused on as a whole.
Keywords: Çalışma ekonomisi; Devlet; Kamu İktisadi Teşekkülleri Capital Accumulation; Labor economics; Özelleştirme; Privatization; Sermaye Birikimi; State; State Economic Enterprises; Turkey; Türkiye